2010
DOI: 10.1038/onc.2010.544
|View full text |Cite
|
Sign up to set email alerts
|

High-level expression of Mastermind-like 2 contributes to aberrant activation of the NOTCH signaling pathway in human lymphomas

Abstract: Inappropriate activation of the NOTCH signaling pathway, for example, by activating mutations, contributes to the pathogenesis of various human malignancies. Here, we demonstrate that aberrant expression of an essential NOTCH coactivator of the Mastermind-like (MAML) family provides an alternative mechanism to activate NOTCH signaling in human lymphoma cells. We detected high-level MAML2 expression in several B cell-derived lymphoma types, including classical Hodgkin lymphoma (cHL) cells, relative to normal B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 43 publications
(92 reference statements)
1
35
0
Order By: Relevance
“…3 Jagged1 is expressed in HRS cells and bystander cells in vivo, 3 and the Notch ligands of the Delta-like family (DLL1, DLL3, DLL4) and Jagged2 are expressed in cultured HRS cells to activate Notch signaling. 4 We further demonstrated that absence of the main Notch1 inhibitor Deltex1 and high-level expression of the Notch co-activator of the Mastermind-like family contribute to deregulated Notch signaling in HRS cells. 4,5 Notch1 activity reduces the expression of the B cell transcription factors E12 and E47, and EBF1 and induces the transcription of activated B cell factor 1 (ABF-1).…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…3 Jagged1 is expressed in HRS cells and bystander cells in vivo, 3 and the Notch ligands of the Delta-like family (DLL1, DLL3, DLL4) and Jagged2 are expressed in cultured HRS cells to activate Notch signaling. 4 We further demonstrated that absence of the main Notch1 inhibitor Deltex1 and high-level expression of the Notch co-activator of the Mastermind-like family contribute to deregulated Notch signaling in HRS cells. 4,5 Notch1 activity reduces the expression of the B cell transcription factors E12 and E47, and EBF1 and induces the transcription of activated B cell factor 1 (ABF-1).…”
Section: Introductionmentioning
confidence: 97%
“…4 We further demonstrated that absence of the main Notch1 inhibitor Deltex1 and high-level expression of the Notch co-activator of the Mastermind-like family contribute to deregulated Notch signaling in HRS cells. 4,5 Notch1 activity reduces the expression of the B cell transcription factors E12 and E47, and EBF1 and induces the transcription of activated B cell factor 1 (ABF-1). 5 In addition, Notch1 binds to PAX5 in HRS cells, which might impair PAX5 function.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations